Approximating Common Fixed Points for a Finite Family of Asymptotically Nonexpansive Mappings Using Iteration Process with Errors Terms - Seyit Temir; Adem Kiliçman (Abstract and Applied Analysis)
Let X be a real Banach space and K a nonempty closed convex subset of X. Let Ti:K→K (i=1,2,…,m) be m asymptotically nonexpansive mappings with sequence {kn}⊂[1, ∞), ∑n=1∞(kn-1)<∞, and ℱ=⋂i=1m‍F(Ti)≠∅, where F is the set of fixed points of Ti. Suppose that ainn=1∞, binn=1∞, i=1,2,…,m are appropriate sequences in [0,1] and uinn=1∞, i=1,2,…,m are bounded sequences in K such that ∑n=1∞bin<∞ for i=1,2,…,m. We give {xn} defined by x1∈K,xn+1=(1-a1n-b1n)yn+m-2+a1nT1nyn+m-2+b1nu1n,yn+m-2=(1-a2n-b2n)yn+m-3+a2nT2nyn+m-3 +b2nu2n,…,yn+2=(1-a(m-2)n-b(m-2)n)yn+1+a(m-2)nTm-2nyn+1+b(m-2)nu(m-2)n,yn+1=(1-a(m-1)n -b(m-1)n)yn+a(m-1)nTm-1nyn+b(m-1)nu(m-1)n,yn=(1-amn-bmn)xn+amnTmnxn+bmnumn,m≥2,n≥1. The purpose of this paper is to study the above iteration scheme for approximating common fixed points of a finite family of asymptotically nonexpansive mappings and to prove weak and some strong convergence theorems for such mappings in real Banach spaces. The results obtained in this paper extend and improve some results in the existing literature.